Derek Nurse 2008. Tense and Aspect in Bantu. - Seidel, Frank (AAeO - Afrikanistik-Aegyptologie-Online, 2009)
Written by a Bantuist who has worked in the field of Bantuistics for roughly three decades, this book presents a long awaited effort to assemble and ponder over what is known about tense, aspect, and related subjects in the Bantu languages. Bantu languages, which are spoken south of a line vaguely drawn from northwestern Cameroon to southern Somalia, typically encode a high number of tense aspect categories using a multitude of grammaticalized forms that pay much attention to semantic and functional detail. This book tries to systematize this rather complex situation and identify and describe the general characteristics of how the Bantu languages treat tense and aspect. To achieve this goal the author relied predominately on data from secondary sources and evaluated a sizable number of 210 plus languages.